Metastability of diamond ramp-compressed to 2TPa - Lazicki, A; McGonegle, D; Rygg, JR; Morgan, MG; Braun, DG; Swift, DC; Smith, RF; Heighway, P; Suggit, MJ; Fratanduono, DE; Higginbothom, A; Coppari, F; et al. (Nature, 2021)
Carbon is the fourth-most prevalent element in the Universe and essential for all known life. In the elemental form it is found in multiple allotropes, including graphite, diamond and fullerenes, and it has long been predicted that even more structures can exist at pressures greater than those at Earth’s core1,2,3. Several phases have been predicted to exist in the multi-terapascal regime, which is important for accurate modelling of the interiors of carbon-rich exoplanets4,5. By compressing solid carbon to 2 terapascals (20 million atmospheres; more than five times the pressure at Earth’s core) using ramp-shaped laser pulses and simultaneously measuring nanosecond-duration time-resolved X-ray diffraction, we found that solid carbon retains the diamond structure far beyond its regime of predicted stability. The results confirm predictions that the strength of the tetrahedral molecular orbital bonds in diamond persists under enormous pressure, resulting in large energy barriers that hinder conversion to more-stable high-pressure allotropes1,2, just as graphite formation from metastable diamond is kinetically hindered at atmospheric pressure. This work nearly doubles the highest pressure at which X-ray diffraction has been recorded on any material.